Pulsed Electromagnetic Field Alleviates Intervertebral Disc Degeneration by Activating Sirt1-Autophagy Signaling Network - Zheng, Yi; Mei, Liangwei; Li, Shengyou; Ma, Teng; Xia, Bing; Hao, Yiming; Gao, Xue; Wei, Bin; Wei, Yitao; Jing, Da; Luo, Zhuojing; Huang, Jinghui (Frontiers in Bioengineering and Biotechnology, 2022)
Intervertebral disc (IVD) degeneration is regarded as a major contributor to low back pain (LBP), causing serious economic burden on individuals and society. Unfortunately, there are limited effective treatment for IVD degeneration. Pulsed electromagnetic field (PEMF) is an economical and effective physical therapy method, with reduced side-effects. It offers certain protection to a number of degenerative diseases. Therefore, understanding the underlying mechanism of PEMF on IVD is important for improving the PEMF therapeutic efficiency. In this study, PEMF up-regulated extracellular matrix (ECM) related genes in degenerated nucleus pulposus (NP) cells. It also increased SIRT1 expression and promoted autophagy in degenerated NP cells. In contrast, the autophagy suppressor 3-methyladenine (3-MA) reversed the beneficial effect of PEMF on ECM production. Similarly, the SIRT1 enzyme activity suppressor EX 527 also inhibited the effect of PEMF on autophagy and ECM production in NP cells, thereby suggesting that PEMF regulated ECM-related genes expression through SIRT1-autophagy signaling pathway. Lastly, PEMF significantly reduced IVD degeneration in a rat model of IVD degeneration in vivo. In summary, our study uncovers a critical role of SIRT1-dependent autophagy signaling pathway in ECM protection and thus in the establishment of therapeutic effect of PEMF on IVD degeneration.